High expression of DNA methyltransferase 1 in Kazakh esophageal epithelial cells may promote malignant transformation induced by N-methyl-N′-nitro-N-nitrosoguanidine. (September 2019) - Chen, Y; Feng, H; Zhang, H; Li, X
We examined the role of DNA methyltransferase 1 (DNMT1) in N -methyl- N ′-nitro- N -nitrosoguanidine (MNNG)–induced malignant transformation of Kazakh esophageal epithelial (EE) cells to better understand the pathogenesis of esophageal cancer (EC). The 3-(4, 5)-dimethylthiahiazo (-z-y1)-3, 5-di- phenytetrazoliumromide method and colony formation assays were performed to determine the MNNG dose for malignant transformation. Colony formation assays showed the effects of different frequencies of MNNG exposure and different cell passages on malignant transformation. A nude mouse tumor experiment indicated the malignancy of Kazakh EE cells expressing high DNMT1 levels and of transformed cells. The result shows that when the dose, frequency, and time of MNNG exposure increased, cell morphology became irregular, cell-contact suppression disappeared, and cell tolerance and growth rate increased. Colony formation occurred in the Kazakh-DNMT1 group after 14 transfections and 27 passages. Significant differences in DNMT1 mRNA and protein levels were observed in different types of cells and tumor tissues ( F = 140.644, p < 0.001; F = 105.545, p < 0.001). Our study demonstrated that DNMT1 could promote MNNG to induce malignant transformation of EE cells, and this study will help understand EC better in order to develop appropriate treatment strategies.